2001
DOI: 10.1103/physrevb.64.125104
|View full text |Cite
|
Sign up to set email alerts
|

Nonadiabatic Pauli susceptibility in fullerene compounds

Abstract: Pauli paramagnetic susceptibility χ is unaffected by the electron-phonon interaction in the MigdalEliashberg context. Fullerene compounds however do not fulfill the adiabatic assumption of Migdal's theorem and nonadiabatic effects are expected to be relevant in these materials. In this paper we investigate the Pauli spin susceptibility in nonadiabatic regime by following a conserving approach based on Ward's identity. We find that a sizable renormalization of χ due to electron-phonon coupling appears when nona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…The superconducting phases adopt, in general, either face-centered-cubic (fcc) or primitive cubic structures, in which the three cations occupy the available octahedral and tetrahedral interstitial sites. Charge transfer is essentially complete and the conduction band of C 60 ; which arises from its lowest unoccupied molecular orbital (LUMO) of t 1u symmetry is half filled (Fig. 1).…”
Section: Intercalated Fulleridesmentioning
confidence: 99%
See 3 more Smart Citations
“…The superconducting phases adopt, in general, either face-centered-cubic (fcc) or primitive cubic structures, in which the three cations occupy the available octahedral and tetrahedral interstitial sites. Charge transfer is essentially complete and the conduction band of C 60 ; which arises from its lowest unoccupied molecular orbital (LUMO) of t 1u symmetry is half filled (Fig. 1).…”
Section: Intercalated Fulleridesmentioning
confidence: 99%
“…The high electron affinity of C 60 and the weak intermolecular van der Waals forces between the molecules in the crystal make it an excellent potential host for reductive intercalation chemistry. Indeed, intercalation of solid C 60 with electron donors, like the alkali metals, results in a wealth of intercalated fulleride salts with stoichiometries A x C 60 ; where x can be as low as 1 (CsC 60 ) or as high as 12 (Li 12 C 60 ).…”
Section: Intercalated Fulleridesmentioning
confidence: 99%
See 2 more Smart Citations
“…The detection of isotope effects on various quantities receives a crucial importance in the nonadiabatic framework since it directly probes the nonadiabatic nature of el-ph interaction. In particular it has been shown that nonadiabatic effects give rise to a finite isotope effect on quantities which in conventional ME theory are expected to not show it, for instance the effective electron mass m * [29] and the spin susceptibility χ [30]. The actual discovery of an anomalous isotope effects on these or other quantities represents therefore a precise prediction of the nonadiabatic theory which could be experimentally checked.…”
mentioning
confidence: 99%